Masculinidades neo-coloniales en Talamanca, Caribe sur de Costa Rica (1898-1930) - Menjívar Ochoa, Mauricio (2013)
The article explores what is here called neocolonial masculinity. Neocolonial masculinity seeks to synthesize Walter Mignolo’s proposal on the domains of human experience for understanding the coloniality, and RW Connell’s on the gender structure that explain masculinity. The article discusses how this masculinity was materialized in practices and conceptions of some mestizo men who established social relationships with the Talamanca Bribri indigenous society, in Southern Caribbean Costa Rica (1898-1930). For this purpose, archival sources, statistics, official reports and other contemporary accounts are examined. The research found that theft, appropriation of property, labor exploitation, rape, racialization, and imposition of mestizo knowledge, were elements of neo-colonial male practices to indigenous societies. These practices took refuge in the Costa Rican government’s efforts to extend its control over the Bribri territory. The research also explores some bribri practices of resistance to these neocolonial attacks.